Integrated effects of marketing stimuli on customer loyalty in Palestine grocery supply-chain: does satisfaction perform mediating role? - Haque, A. K. M. Ahasanul; Tarofder, Arun Kumar; Shamsuddoha, Mohammad; Nuruzzaman, Md.; Tor-Kadioglu, Cansu (Springer Nature, 2023)
Grocery stores are a crucial connection in the food delivery system and a fundamental component of the retail industry. Some grocery stores have worked with regional suppliers to benefit the community and the consumer. Palestinian market is uncommon because clients have connected what they manufacture and sell under particular circumstances. This study is, therefore, an integrated examination of the critical influencing factors on the marketing of food products in Palestine. A survey questionnaire was used. An organised, self-administered survey was used to acquire data, and analysis techniques were outlined using Structural Equation Modelling (SEM). According to the findings, relationship marketing and service quality are the crucial brand strategy factors influencing customers’ decisions to purchase groceries and showing how happy and devoted they are to grocery stores. The Palestinian government has greatly benefited from the results of this study of how consumers perceive essential factors that may be considered when formulating future regulations about food and other grocery items.